Role of Total Quality Management and Shared Decision-Making in Enhancing Operational Performance and Enterprise Risk Management Effectiveness - Jehad Abdallah Atieh Afaneh; Khaled Mohammed Ahmed Alqasa (Decision Making: Applications in Management and Engineering, 2025)
This study examines how total quality management (TQM) contributes to enterprise risk management (ERM) effectiveness, with a focus on the mediating role of operational and quality performance and the moderating role of shared decision making. The research aims to provide insights into how quality-driven practices enhance both organizational performance and resilience against risks. A quantitative, cross-sectional design was adopted, using a structured questionnaire administered to a sample of 275 employees engaged in quality and risk-related functions. Total quality management was measured across four key dimensions, while operational and quality performance, enterprise risk management effectiveness, and shared decision making were assessed using established scales. Data were analyzed using SmartPLS to evaluate both the measurement and structural models. The results reveal that TQM has a significant positive effect on both ERM effectiveness and operational and quality performance. Operational and quality performance significantly mediates the TQM–ERM relationship, while shared decision making strengthens the link between TQM and operational and quality performance. This study integrates quality and risk management research, demonstrating that TQM’s impact on ERM is enhanced through performance improvements and participatory governance, offering both theoretical advancement and practical guidance for building resilient organizations.